EXPLANATION END DEVELOPMENT OF COMBINED TOOL CORE DRILL TAP WITH THE NEW CUTTING SCHEME - N. M. Vagabov; A. Z. Kurbanov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The results of the research on thread making in hard-to-machine materials are given. A new technology with use of combined core drill tap allowing the stabilization of the stock for further processing, correction of the hole axis and provision of larger severity of the tool is developed. The factors influencing on the quality and performance of thread making reliability and working capacity of the tap cutting tool are identified. The recommendations on tool friction and heating reduce in order to provide the larger severity and durability are given.